Proyek Javhistografi untuk Mengembangkan Kreativitas dan Triliterasi Membuat Teks Deskriptif Kreatif Berbahasa Jawa - Agung Vendi Setyawan (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
The Javhistografi poster project is a local content-based learning project for the Java language. This learning aims to develop creativity and trilateration (literacy, digital, cultural, and civic literacy) in the sixth-grade students of State Elementary School Tamanan 2 Kalasan with a total of 26 children in Semester I of the 2019/2020 Academic Year. The research method refers to the ADDIE development model (analysis, design, implementation, and evaluation) carried out by a combination model method. The results obtained were: (1) children who worked together in groups to complete tasks were 76.92% predicated B (good) and 23.08% predicated A (very good); (2) student skill assessment showed that 11.54% had B+ predicate and 88.46% B predicated; and (3) material understanding of temple and museum relics reached 63% and 79%, respectively. Student responses indicate that: (1) 96.15% agree that this learning model fosters independence; (2) as many as 88.46% agree that this learning model trains collaboration between students; (3) as many as 76.92% consider learning fun; (4) as much as 53.85% motivate students to want to read; (5) as many as 92.31% of students think that the device can be used for useful things; (6) as many as 96.15% of students feel they are participating in the effort to preserve historical heritage; (7) as many as 88.46% of students can learn graphic design; and (8) 96.15% thought that the Kahoot quiz was fun for an evaluation tool.